(3fbd Yf cJGH ZGjI GdMcje GdeLQjWis
(3ChdgG (B:s
(3hGYde Cf gPG GdYde hGdhbha Ydjg EdG def ai WHGYJg Pdc hEdi gPG CTGQ CQSWh ai cJGH GdCSWeGNjS s
(3BNQgG (B:s
(3hcGf gPG SHHkG dELJdGH cdGe GdMcje CQSWh ai Pdc aJage s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(20981) s
Keywords: (3GdadSaI hGdefWbs